Energy Audit and Analysis of an Institutional Building under Subtropical Climate - Yazed Yasin Ghadi; Ali M. Baniyounes (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Evaluation and estimation of energy consumption are essential in order to classify the amount of energy used and the way it is utilized in building. Hence, the possibility of any energy savings potential and energy savings opportunities can be identified. The intention of this article is to study and evaluate energy usage pattern of the Central Queensland University campus’ buildings, Queensland, Australia. This article presents the field survey results from the audit of an office building and performance-related measurements of the indoor environmental parameters, for instance, indoor air temperature, humidity and energy consumption concerned to the indoor heating and cooling load. Monthly observed energy usage information was employed to investigate influence of the climate conditions on energy usage.